The Influence of Self-Efficacy and School Culture on the Job Satisfaction of RK Bintang Timur Private Elementary School Teachers - Normalina Saragih; Effendi; Sherly; Marto Silalahi; Liper Siregar; Herman (CV. Creative Tugu Pena, 2024)
The objectives of this research are: 1. To find out the picture self efficacy school culture and teacher job satisfaction. 2. To know the influence self efficacy and school culture on teacher job satisfaction both simultaneously and partially. This research uses a library research design and field research. The population in this study was all 33 teachers. The types of data used are qualitative data and quantitative data. The data sources used are primary data and secondary data. Data collection was carried out by interviews, documentation and questionnaires. The research instrument test used is the validity and reliability test. Data analysis techniques consist of normality tests, qualitative descriptive analysis and quantitative descriptive analysis. The results of this research can be concluded as follows: Self efficacy teachers are good, school culture is still strong enough, and teacher job satisfaction is high. There is a strong and positive relationship between self efficacy with school culture, teacher job satisfaction. The high and low level of teacher job satisfaction can be explained by the contribution of self efficacy And school culture. To optimize self efficacy teachers are optimized by trying to make the work environment comfortable. To increase teacher job satisfaction with a review by the foundation with requests from school principals regarding salaries and other compensation received by teachers by comparing them with government regulations regarding UMR and also salaries in other schools that are parallel to the schools being managed